The possibility of patient-centered dietetic intervention in the context of health literacy in Hungary - Szucs, Zsuzsanna; Ercsey, Ida; Horkai, Anita; Feith, Helga Judit (Frontiers in Nutrition, 2026)
IntroductionNon-communicable diseases (NCDs) accounted for 74% of global deaths in 2024, with over 41 million people dying. The WHO has identified reducing behavioral and metabolic risk factors as a priority intervention. In modern healthcare, patient-centered care plays a key role by addressing individual needs, lifestyles, and motivations, thereby enhancing the effectiveness of prevention and behavior change. Food-based dietary guidelines (FBDG), such as Hungary’s OKOSTÁNYÉR®, are vital in prevention and medical nutrition therapy. However, the effectiveness of such dietary interventions largely depends on individuals’ health literacy.ObjectivesThis study aimed to explore the relationship between health literacy, dieting habits, dietary counseling, and awareness of the local FBDG recommendations.MethodsThis cross-sectional study was conducted in February 2023 on a representative sample (N = 500) of the adult Hungarian population, using the CAWI method. Data were collected with the validated HLS-EU 47-item questionnaire and additional custom items on health status, dieting, and awareness of the local FBDG. Health literacy indexes were calculated using validated thresholds. Descriptive statistics, chi-square tests, ANOVA, and multivariate regression analyses were applied (p < 0.05).ResultsA total of 77.4% of respondents had low (insufficient or problematic) health literacy. Higher education levels and younger age were significantly associated with better health literacy. Chronic diseases were more prevalent in low health literacy groups. About 32.4% of respondents followed a medically indicated diet, and 36.8% had received dietary counseling. Awareness of the local FBDG was relatively low (20.8%), particularly among men and those with lower education.ConclusionPatient-centered care necessitates a high level of health literacy, enabling patients to actively participate in their therapy. Findings of the study highlight that low health literacy in the Hungarian population poses a major challenge to the success of dietary interventions. Targeted health communication strategies and tailored dietetic support are essential to improve the effectiveness of personalized nutrition care, particularly among vulnerable groups with limited health literacy.